2008
DOI: 10.3152/030234208x389701
|View full text |Cite
|
Sign up to set email alerts
|

Pathways to the entrepreneurial university: towards a global convergence

Abstract: This paper analyzes the transition to the entrepreneurial university as part of a broader shift to a knowledge-based economy, arising from a complex interplay between exogenous (top-down) and endogenous factors (bottom-up) of a more or less similar nature, combined in different ways in different countries. Drawing on the experience of four countries (US, Sweden, Japan and Brazil) with different institutional trajectories and degrees of academic entrepreneurial transformation, under varying degrees of state con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
90
1
16

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(107 citation statements)
references
References 23 publications
0
90
1
16
Order By: Relevance
“…Thus, the role of entrepreneurship in university activity depends on several institutional factors: institutional autonomy, the allocation of funding streams, governance mechanisms and the surrounding entrepreneurial climate. Furthermore, a distinction can be made between the exogenous (top-down) and endogenous (bottom-up) factors that shape universities' transformations into entrepreneurial institutions [Etzkowitz et al, 2008]. Exogenous factors include external shocks, such as the 2008 economic crisis and subsequent grand societal challenges, which then called for knowledge-based and sustainable solutions.…”
Section: Figure 1 the Knowledge Triangle Of Education Research And mentioning
confidence: 99%
“…Thus, the role of entrepreneurship in university activity depends on several institutional factors: institutional autonomy, the allocation of funding streams, governance mechanisms and the surrounding entrepreneurial climate. Furthermore, a distinction can be made between the exogenous (top-down) and endogenous (bottom-up) factors that shape universities' transformations into entrepreneurial institutions [Etzkowitz et al, 2008]. Exogenous factors include external shocks, such as the 2008 economic crisis and subsequent grand societal challenges, which then called for knowledge-based and sustainable solutions.…”
Section: Figure 1 the Knowledge Triangle Of Education Research And mentioning
confidence: 99%
“…(Etzkowitz et al 2000: 313; see also Etzkowitz et al 2008) The first traced publication referring to entrepreneurial behavior at a European university dates back to the early 1990s when Maassen and van Buchem (1990) described how the leadership structures at the University of Twente in the Netherlands turned an institutional crisis into a strategic opportunity. The result was the reinvention of a relatively marginalized regional university into a dynamic and innovative academic establishment.…”
Section: The Entrepreneurial Turn In European Higher Education?mentioning
confidence: 99%
“…Etzkowitz, Ranga, Benner, Guaranys, Maculan, and Kneller, (2008) conducted a multi-nation survey of endogenous and exogenous factors driving knowledge management in the United States, Japan, Sweden, and Brazil. Their study concluded that American higher education institutions as well as those in Asia, Europe, and Latin America have come to see knowledge management as central to their raison d'etre in today's know economy.…”
Section: Higher Educationmentioning
confidence: 99%